Analysis of Phenological Observations of Soybean 6310 and 7213 Collection Samples - Khayridinova Ranokhon Qakhramon kizi; Yuldasheva Rano Abdurashidovna; Mirzaeva Iroda Turdalievna (Zien Journals, 2023)
In this article, ew describe the results of the phenological observation and analisis of soybean germination, flovering and pot phases for 6310 and 7213 samples
Keywords: Soybean collections; phenological observation